The de-industrialization process in South Italy and the new industrial policies in Europe - Michele Sabatino (European Regional Science Association (ERSA), 2016)
Italy went through the economic crisis intensified after World War II to the present day. Compared to 2007, GDP fell by more than 7 percentage points. The industry is the sector where the decline in production, both in the manufacturing component is in one of the buildings, was stronger. It is a decline that is impacting negatively on the production potential and future prospects of the Italian economy but also on the potential recovery of Southern Italy. The crisis of the industrial system reflects the difficulties of the Italian economy to adapt to the major changes that have affected the international economic environment in the last two decades and that the economic crisis has radicalized: the process of globalization and integration of real and financial markets; European integration, which culminated in the introduction of the Euro; change of technological paradigm initiated by new information and communications technology. Three factors have resulted in a sharp and sudden increase in competitive pressure. The Italian production system failed to react quickly partly because of structural problems that afflict him for too long now. In this situation of structural disadvantage was added, finally, the weakness of domestic demand in the last decade, as a result of tensions in the credit market and the public finance policies, has culminated in a significant contraction. This process of de-industrialization and marginalization of the economy of Southern Italy must be opposed to start a real recovery of competitiveness. To do whatever is necessary to support appropriate public policies that can have a positive effect on the entire Italian economic system. With this target the present paper briefly describes the evolution, especially recently, the Italian industrial system. It examines, first, the global environment and the state of competitiveness of the Southern Italy industrial sector and, subsequently, the main factors that affect competitiveness. It plots, finally, some reflections and working hypotheses for the economic and industrial policy.
Keywords: 330; Deindustrialization; Industrial Compact; Industrial policies; Competitiveness; Investments